Sûfî gözüyle hac - (:unkn) unknown (My University, 2010)
Sûfîler eserlerinde haccın mânevî yönüne temas etmişler, hac esnâsındaki eylemlerin sembolik anlamlarını açıklamaya çalışmışlardır. Hacca gitmek için hazırlık yapan kişinin âile ve komşularına karşı görevlerini ihmâl etmemesi gerektiğini anlatan menkıbelere eserlerinde yer vermişlerdir. Sûfîlere göre insan Allah’ı kalbi yani yüksek idrakiyle tanıyabileceği için sûfîler âriflerin kalbini Kâbe’den daha üstün saymışlardır. Bazı sûfîler de hac esnâsında kalplerine doğan keşf ve ilhâmları kaleme almışlardır.

Sufis spoke about the spiritual side of hajj, and tried to explain symbolic meanings of the hajj rituals. They wrote down mystical anecdotes that people, who are getting ready for hajj, should not neglect their family members and neighbors. According to Sufis, since human being can know Allah by his high level of comprehension, they considered the heart of a sage superior than the Ka‘bah. Some Sufis wrote down their inspirations and revelations, which appeared in their hearts during hajj.
Hajj from sufi perspective
Keywords: Din Bilimi